Optimalisasi Pembinaan Karakter Siswa Melalui Pendidikan Akhlak Pada MTS Putra Ddi Mangkoso Kabupaten Barru - Syukri Syukri (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2021)
This study aims to determine the optimalization of the character building of students through moral education at MTs Putra DDI Mangkoso, Barru Regency. Researchers use this type of qualitative research; research on problem disclosure as there is data analysis using observations and interviews. The approach used; Psychological, sociological, and theological with qualitative methods and data analysis in the form of data reduction, data presentation, and conclusion or verification. The results of this study indicate, the implementation of character education at MTs Putra DDI Mangkoso Barru Regency conceptually refers to 4 out of 18 national characters internalized into Madrasah programs, it's just that not all of the inculcation of character values ​​goes as expected, this is because there are still technical obstacles such as disciplinary students, parents who pay less attention to their children, students with lower economic backgrounds, as well as some infrastructure. that does not support activities. Character education for students at MTs Putra DDI Mangkoso Barrud Regency is carried out using the Reward and punishment Method, the method of motivation, the method of habituation, and the exemplary method.